Answer:
Hey There!
Let's solve...
Here it is a rectangular floor with length =21 cm and width =15cm
So
![area = l \times w \\ = 21 \times 15 \\ = 315 {ft}^{2} \\ \\](https://tex.z-dn.net/?f=area%20%3D%20l%20%5Ctimes%20w%20%5C%5C%20%20%3D%2021%20%5Ctimes%2015%20%5C%5C%20%20%3D%20315%20%7Bft%7D%5E%7B2%7D%20%5C%5C%20%20%5C%5C%20%20)
So now We need to convert it to yards square
![315ft^{2} \times \frac{ {1yd}^{2} }{ {9ft}^{2} } \\ \\ = \cancel{315ft^{2}} \: ^{35} \times \frac{ {1yd}^{2} }{ \cancel{9 {ft}^{2} }} \\ \\ = 35 {yd}^{2}](https://tex.z-dn.net/?f=315ft%5E%7B2%7D%20%5Ctimes%20%20%5Cfrac%7B%20%7B1yd%7D%5E%7B2%7D%20%7D%7B%20%7B9ft%7D%5E%7B2%7D%20%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%5Ccancel%7B315ft%5E%7B2%7D%7D%20%20%5C%3A%20%5E%7B35%7D%20%20%5Ctimes%20%20%5Cfrac%7B%20%7B1yd%7D%5E%7B2%7D%20%7D%7B%20%5Ccancel%7B9%20%7Bft%7D%5E%7B2%7D%20%7D%7D%20%20%5C%5C%20%20%5C%5C%20%20%3D%2035%20%7Byd%7D%5E%7B2%7D%20%20)
So how this 9 ft^2 came??
Let's know
![ft \to \: yards \\ \\ 3ft = 1yd \\ \\ {3ft}^{2} = {1yd}^{2} \\ \\ \boxed{ {9ft}^{2} = {1yd}^{2}}](https://tex.z-dn.net/?f=ft%20%5Cto%20%5C%3A%20yards%20%5C%5C%20%20%5C%5C%203ft%20%3D%201yd%20%5C%5C%20%20%5C%5C%20%20%7B3ft%7D%5E%7B2%7D%20%3D%20%20%7B1yd%7D%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cboxed%7B%20%7B9ft%7D%5E%7B2%7D%20%3D%20%20%7B1yd%7D%5E%7B2%7D%7D%20%20%20)
<h2>I hope it is helpful to you...</h2><h3>Cheers!_______</h3>
Answer:
Cube
Step-by-step explanation:
It makes a cube
Answer:
-16
Step-by-step explanation:
5^2+7/5-7
32/-2
-16
(4*3)+-4=8, this is just how to put it in the equation
Answer:
f(x)=a(x - h)2 + k
Much like a linear function, k works like b in the slope-intercept formula. Like where add or subtract b would determine where the line crosses, in the linear, k determines the vertex of the parabola. If you're going to go up 2, then you need to add 2.
The h determines the movement horizontally. what you put in h determines if it moves left or right. To adjust this, you need to find the number to make the parentheses equal 0 when x equals -2 (because moving the vertex point to the left means subtraction/negatives):
x - h = 0
-2 - h = 0
-h = 2
h = -2
So the function ends up looking like:
f(x)=a(x - (-2))2 + 2
Subtracting a negative cancels the signs out to make a positive:
f(x)=a(x + 2)2 + 2
Step-by-step explanation: